MicroRNA function in the nervous system - Fiore, Roberto; Khudayberdiev, Sharof Abdumalikovich; Saba, Reuben; Schratt, Gerhard (Progress in molecular biology and translational science, 2011)
MicroRNAs (miRNAs) are an extensive class of small noncoding RNAs that control posttranscriptional gene expression. miRNAs are highly expressed in neurons where they play key roles during neuronal differentiation, synaptogenesis, and plasticity. It is also becoming increasingly evident that miRNAs have a profound impact on higher cognitive functions and are involved in the etiology of several neurological diseases and disorders. In this chapter, we summarize our current knowledge of miRNA functions during neuronal development, physiology, and dysfunction.